2019
DOI: 10.3390/s19132985
|View full text |Cite
|
Sign up to set email alerts
|

A Cancelable Iris- and Steganography-Based User Authentication System for the Internet of Things

Abstract: Remote user authentication for Internet of Things (IoT) devices is critical to IoT security, as it helps prevent unauthorized access to IoT networks. Biometrics is an appealing authentication technique due to its advantages over traditional password-based authentication. However, the protection of biometric data itself is also important, as original biometric data cannot be replaced or reissued if compromised. In this paper, we propose a cancelable iris- and steganography-based user authentication system to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…In [32], a steganography scheme based CBRS for iris templates is presented to preserve user verification and safeguard the original unique iris information for IoT remote access applications. The main benefit of the suggested CBRS is that it integrates the data steganography process to generate the cancelable biometric templates to mitigate the issue of traditional CBRSs that depend on random projection and permutation techniques that are dependent on key-dependent transforms.…”
Section: Related Cancelable Biometrics Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [32], a steganography scheme based CBRS for iris templates is presented to preserve user verification and safeguard the original unique iris information for IoT remote access applications. The main benefit of the suggested CBRS is that it integrates the data steganography process to generate the cancelable biometric templates to mitigate the issue of traditional CBRSs that depend on random projection and permutation techniques that are dependent on key-dependent transforms.…”
Section: Related Cancelable Biometrics Workmentioning
confidence: 99%
“…For additional verification for the competence of the suggested algorithm for consistent cancelable recognition model, further comparisons are carried out for contrasting the outcomes of the suggested cancelable system with the recent literature CBRSs in [12,13,15,16,17,21,24,32,33,35,49]. We contrasted the average numerical security assessment of the FAR, EER, AROC, and FRR findings of the suggested CBRS with the previous recent CBRSs in [12,13,15,16,17,21,24,32,33,35,49] as summarized in Table 13. The offered outcomes in Table 13 demonstrated that the FAR, EER, AROC, and FRR of the suggested optical cryptography algorithm based CBRS are superior and highly contrasted as compared to the previous CBRSs.…”
Section: H Comparative Analysismentioning
confidence: 99%
“…Military applications have strict security requirements and therefore require high recognition accuracy. Iris-based recognition systems usually outperform systems using fingerprints or face, thus in this paper, we present an iris recognition system as an example for showing how to perform personal recognition with the iristhis approach is based on [70].…”
Section: B Identification Of Personnel Using Biometricsmentioning
confidence: 99%
“…Ii is in the ranging from 0 to 255. As in the method used in [70], each of these integer values is quantized with the following equation,…”
Section: B Identification Of Personnel Using Biometricsmentioning
confidence: 99%
See 1 more Smart Citation